1991
DOI: 10.1093/oxfordjournals.aje.a115839
|View full text |Cite
|
Sign up to set email alerts
|

Birth Weight and Cardiovascular Malformations: A Population-Based Study

Abstract: Mean birth weights were evaluated in infants with D-transposition of the great arteries, tetralogy of Fallot, endocardial cushion defect, hypoplastic left heart syndrome, pulmonary stenosis, aortic stenosis, coarctation of the aorta, ventricular septal defect, and atrial septal defect in a population-based case-control study of congenital cardiovascular malformations in residents of Maryland, Washington, D.C., and northern Virginia (1981-1987). Study subjects were liveborn singletons without extracardiac anoma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
77
3
4

Year Published

2000
2000
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 128 publications
(94 citation statements)
references
References 0 publications
10
77
3
4
Order By: Relevance
“…In particular, there are higher incidence rates of coarctation of the aorta, doubleinlet left ventricle, hypoplastic left heart, truncus arteriosus, double-outlet right ventricle (a diagnostic category we did not use), and atrioventricular septal defect among stillbirths. Interestingly, this spectrum of malformations is similar to that shown in Fig 2 and those reported by Rosenthal et al 31 and Kramer et al, 32 as discussed above. Whether the increased prevalence of cardiovascular malformations among preterm infants and the increase in stillbirths reported by Hoffman 34 suggest clues to the cause is difficult to say.…”
Section: E836supporting
confidence: 90%
See 1 more Smart Citation
“…In particular, there are higher incidence rates of coarctation of the aorta, doubleinlet left ventricle, hypoplastic left heart, truncus arteriosus, double-outlet right ventricle (a diagnostic category we did not use), and atrioventricular septal defect among stillbirths. Interestingly, this spectrum of malformations is similar to that shown in Fig 2 and those reported by Rosenthal et al 31 and Kramer et al, 32 as discussed above. Whether the increased prevalence of cardiovascular malformations among preterm infants and the increase in stillbirths reported by Hoffman 34 suggest clues to the cause is difficult to say.…”
Section: E836supporting
confidence: 90%
“…21 Although birth weight was recorded for all cases in our register, our analysis was on the basis of gestational age alone. Rosenthal et al 31 reported a case-control study of birth weight in relation to estimated gestational age among singleton infants with a limited range of isolated cardiovascular malformations. They found a significant increase in the likelihood of being small for gestational age among infants with tetralogy of Fallot, complete atrioventricular septal defect, hypoplastic left heart, or large ventricular septal defect.…”
Section: E836mentioning
confidence: 99%
“…Pela análise univariada, foi observada associação entre presença de cardiopatia congênita e peso ao nascimento ≤ 2.500 g, o que também é descrito na literatura [29][30][31] …”
Section: Objetivosunclassified
“…1 and 2, the Baltimore-Washington Infant Study, and the New England Regional Infant Cardiac Program are but some of the important summaries of clinical outcomes addressing both specific lesions and outcomes of infants with congenital heart disease in disparate areas of the United States. [155][156][157][158][159][160] Other strategies to reduce mortality and to enhance cohort inclusion are regionalization and the development of standards for practice. [161][162][163][164] There is increasing evidence that regionalization can reduce surgical mortality and thus enhance outcomes.…”
Section: Outcome Analysis In Congenital Heart Diseasementioning
confidence: 99%